Gypsum Crystallization in the Presence of Cr3+ and Citric Acid - KIRAN YILDIRIM, BERÇEM; SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-BLACKWELL, 2010)
Reactive crystallization of calcium sulfate dihydrate (gypsum) was investigated at pH 3.5 and 65 degrees C in the presence of citric acid and Cr3+ ions. Concentrations of both additives varied between 0 and 4000 ppm. The combined effect of additives on crystal size distributions, filtration characteristics, and crystal morphology were investigated and discussed. It was found that the effect of citric acid on gypsum morphology was suppressed in the presence of Cr3+ ions. The change of morphology is related to the complex formation between Cr3+ ions and citric acid at high ion concentrations.
Keywords: Crystallization; Filtration; Gypsum; CALCIUM-SULFATE DIHYDRATE; SCALE FORMATION; KINETICS; GROWTH